Does the connotation of the word KAIMIETIS ‘countryman’ change? - Kvašytė, Regina; Župerka, Kazimieras; Maskuliūnienė, Džiuljeta (Lietuvių kalba, 2020)
The recording of the derogatory meaning of the kaimietis ‘countryman’ in the Dictionary of the General Lithuanian Language and the recently spread statement among linguists that a new negative connotation (meaning) of the word kaimietis has appeared, led to the analysis of the usage of the word. For the research of sociolinguistic and stylistic interpretation of the word, material was collected from the Fiction and Press sections of the Corpus of the Contemporary Lithuanian Language (CCLL). In addition, examples from dictionaries, media, works of Lithuanian fiction and other contemporary texts were collected.Since many years, in its main meaning, the word kaimietis has remained functionally stylistically and evaluatively neutral word meaning a rural resident (less often a person of rural origin). In almost one-fifth of the examined contexts of the word kaimietis, the word itself has an evaluative tone that is emphasized in one way or another; the number of contexts of positive and negative evaluation differs little. 1375 examples found in CCLL of usage of nouns kaimietis ‘countryman’, kaimietė ‘countrywoman’ in all forms in the contexts were distributed according to the content as follows: neutral (~ 83%), negative (~ 10%) and positive (~ 7%).From the modern language usage data, it is clear that it is purposeful to talk about the systematic connotation of the noun kaimietis when its meaning is not a “rural resident” (“peasant”) or “a person of rural origin”, but a certain stereotype, usually with negative uneducated and similar characteristics. The recording of the derogatory meaning of the kaimietis, kaimietė in the Dictionary of the General Lithuanian Language is a case of legitimation of the penetration of low-style means of expression into neutral-style discourse and such manifestations. The fact that the word countryman, having the derogatory meaning “ignorant, etc.”, does not necessarily apply to the countryman, does not in any way diminish the denigration of the rural man. The one-sided negative attitude towards the countryman arises from a superficial knowledge of the village, certain ideological attitudes, as well as from a person’s spiritual immaturity, urban pride; it spreads and has an effect because of the urban territories.Contexts of unfavorable evaluation are not a new phenomenon: reflections of a negative kaimietis connotation also exist in old phraseology, interwar and later texts in journalism and fiction. Negative evaluation of rurality is especially strong in slang, jargon, and low culture in general. This connotation is reinforced by the denigration of the language of the villagers. On the other hand, the public has always been characterized by solidarity with the rural man, the ability to appreciate what is good and beautiful in the village.
Keywords: word connotation; meaning; evaluative tone